Production of biodiesel from Waste cooking oil using Biochar Based Heterogeneous Catalyst - ArchanaH, ArchanaH; BanupriyaD, BanupriyaD; SaranyaR, SaranyaR; SivajiR, SivajiR; Diya P, Diya P; Sowrabhi H, Sowrabhi H (Journal of Neonatal Surgery, 2025)
Biodiesel (mono-alkyl esters) is an alternative fuel which can be made from renewable biological sources such as vegetable oils and animal fats. The aim of the present work is to produce biodiesel from waste cooking oil using bio char based heterogeneous catalyst. The waste cooking oil was collected from near-by hotels and restaurants. The collected oil was pretreated. Then the biochar was produced from sugarcane bagasse. The produced biochar was doped with Zinc Oxide. The characteristic and morphology of the obtained ZnO doped nanocatalyst by using co-precipitation was studied using SEM and FTIR. The doped bio char was used as heterogeneous catalyst for the transesterification process. The optimization of the transesterification process was do neat 60ºC. The weight % of the catalyst was added as 1%, 3%, 5%. The transesterification process was carried out by mixing the pretreated oil with the prepared catalyst to produce biodiesel. The produced biodiesel was analyzed and the presence of the fatty acid ester was checked. The waste which is known as glycerol remained after the production of biodiesel was given to the chemical industries. The motive is to produce biodiesel with 0% waste. The produced biodiesel was characterized by GCMS. For the analyses of the GCMS sample in three different types of ratio 1:6, 1:9, 1:12. We got the optimum yield of 91% at 60ºC, 5 wt% of catalyst, 1:12 oil to ethanol ratio and reaction time was 1 hour 30 minutes.